Intelligence and Cognitive Development: Three Sides of the Same Coin - de Ribaupierre, Anik (J Intell, 2017)
Research on intelligence, mainly based on correlational and factor-analytical work, research on cognitive development, and research in cognitive psychology are not to be opposed as has traditionally been the case, but are pursuing the same goal, that is, understand how the human being adapts to his/her own, complex environment. Each tradition of research has been focusing on one source of variation, namely situational differences for cognitive psychology, individual differences for psychometrics, and age differences for developmental psychology, while usually neglecting the two other sources of variation. The present paper compares those trends of research with respect to the constructs of fluid intelligence, working memory, processing speed, inhibition, and executive schemes. Two studies are very briefly presented to support the suggestion that tasks issued from these three traditions are very similar, if not identical, and that theoretical issues are also similar. We conclude in arguing that a unified vision is possible, provided one is (a) interested in the underlying processes and not only in the experimental variations of conditions; (b) willing to adopt a multidimensional view according to which few general mechanisms are at work, such as working memory or processing capacity, inhibition, and executive schemes; and (c) granting a fundamental role to individual differences.